Fast forward modeling and response analysis of extra-deep azimuthal resistivity measurements in complex model - Zhang, Pan; Deng, Shaogui; Yuan, Xiyong; Liu, Fen; Xie, Weibiao (Frontiers in Earth Science, 2025)
The Extra-Deep Azimuthal Resistivity Measurements (EDARM) tool, as an emerging technology, can effectively identify geological interfaces within a range of several tens of meters around the borehole, providing geological structures for directional drilling, and effectively improving reservoir encounter rates and enhancing oil and gas recovery rates. However, the signal is jointly affected by interfaces located both ahead of the drill bit and around the borehole, making it impossible to directly obtain the interface position from the signal. Considering the increased detection range of EDARM and the requirements for computational efficiency, this paper presents a 2.5-dimensional (2.5D) finite element method (FEM). By leveraging the symmetry of simulated signals in the spectral domain, the algorithm reduces computation time by 50%, significantly enhancing computational efficiency while preserving accuracy. During the geosteering process, fault and wedge models were simulated, and various feature parameters were extracted to assess their impact on the simulation outcomes of EDARM. The results show that both Look-around and Look-ahead modes exhibit sensitivity to changes in the angle of the geological interface. Crossplot analysis allows for effective identification of interface inclinations and the distances between the instrument and the geological interface. This recognition method is quick, intuitive, and yields reliable results.